Граматичні лексикографічні системи з флективним і аглютинативнимм компонентом словозміни - Любченко, Т.П.; Шевченко, І.В.; Широков, К.В. (Мовознавство, 2013)
У статті подано концептуальні моделі словозмінної системи мов із флективним компонентом словозміни, мов із флективним та аналітичним компонентами, а також мов з аглютинативним компонентом. Описано технологію побудови граматичних лексикографічних систем, їхню структуру та функції. Grammatical lexicographical systems (GLS) are being developed in the Ukrainian Lingua-Information Fund of the National Academy of Sciences of Ukraine for different languages within the framework of research works to create the National dictionary database of Ukraine. The article presents a conceptual model of inflectional systems of languages with the flectional component in inflection, those with the flectional and the analytical component, and those with the agglutinative component. The technology of construction of GLS, their structure and functions are described. In addition to its main purpose (use in the automatic text processing) the GLS are also used in the study of inflectional systems of respective languages. The article, in particular, deals with the results of research on the parameters of incompleteness and variability of the inflectional paradigm in Russian. The data obtained can be used in the typological studies of the inflectional systems of the inflected languages.